Localization and Study of Histochemical Effects (Journal of Sciences, Islamic Republic of Iran)
A high capacity for accumulation of Mn was reported for sunflower plants. Localization of excess Mn is therefore of special interest for understanding metal tolerance mechanisms in this species. In this study, structural and histochemical alterations caused by Mn accumulation in leaves were investigated in sunflower (Helianthus annuus L. cv. Azar-ghol) plants grown in nutrient solution. In the presence of excess Mn (up to 100 µM) shoot and root accumulated up to 4-5 mg Mn g-1DW concomitant with an increased activity of peroxidase, but not catalase. Symptoms were observed in mature leaves of plants as small dark-brown to black spots associated with the leaf trichomes. In the short uni- or multi-cellular leaf hairs the entire trichome was blackened, while there was a blackened basal cell or tip cell in the long linear multi-cellular trichomes. No dark deposition was observed either in the tip or in the base of the spiral multi-cellular trichomes. Epi-illumination method revealed a dense dark discoloration of small veins of areoles in mature leaves of Mn treated plants with a high auto-fluorescence, suggesting accumulation of phenolics. Histochemical methods for callose, lipids, lignin and proteins showed no change in Mn treated leaves; while a significant decrease of starch grains was observed using polysaccaride identification test. Bleaching of dark spots by ethanol and lack of auto-fluorescence in the locations of leaf trichomes as well as result of histochemical methods for free and bound phenolics suggested strongly that the dark spots are the locations of MnO2 deposits.